2018
DOI: 10.3221/igf-esis.44.09
|View full text |Cite
|
Sign up to set email alerts
|

Development of an optimal process for friction stir welding based on GA-RSM hybrid algorithm

Abstract: ABSTRACT. Performance of Friction Stir Welding (FSW) as a solid-state process is approved in several engineering applications, especially aluminum industries. Identification of mechanical behavior of the associated welded zone is necessary due to these extensive applications of FSW. In this study, considering the effect of rotational and forward speed of welding tool on the mechanical properties of welded region, a hybrid optimization method based on combination of Genetic Algorithm (GA) and Response Surface M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Tool rotation speed, welding/traverse speed, tool inclination angle, axial force, and plunge depth are the primary variables. Furthermore, it has been reported that the rotational speed of the tool along with traverse speed in the second position is the most significant parameter for impact strength [6], elongation percentage [7], and other mechanical properties of the weld [8]. This was positively verified by [9] through experimental and numerical investigation for lap joints of high-density polyethylene (HDPE).…”
Section: Introductionmentioning
confidence: 90%
“…Tool rotation speed, welding/traverse speed, tool inclination angle, axial force, and plunge depth are the primary variables. Furthermore, it has been reported that the rotational speed of the tool along with traverse speed in the second position is the most significant parameter for impact strength [6], elongation percentage [7], and other mechanical properties of the weld [8]. This was positively verified by [9] through experimental and numerical investigation for lap joints of high-density polyethylene (HDPE).…”
Section: Introductionmentioning
confidence: 90%
“…The model was able to predict the ultimate tensile strength of FSW joints within the 95% confidence level. Khansare et al [17] proposed a hybrid optimization methodology based on the combination of the RSM and a genetic algorithm (GA) [18] to approximate the optimal welding speed and tool rotational speed in which a maximum ultimate tensile strength could be achieved.…”
Section: State Of the Art-use Of Optimization Algorithms In The Fieldmentioning
confidence: 99%
“…Few researchers have used the optimization technique in the friction stir welding field but very little in case of UWFSW. The ANFIS Integrated Hybrid Methods are provided in this study for successfully modeling the UWFSW parameters with performance reaction values [20][21][22]. The RSM-GA Integrated Hybrid Methods are suggested in this research for modeling the UWFSW parameters.…”
Section: Introductionmentioning
confidence: 99%